2013
DOI: 10.1371/journal.pone.0053880
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Regulation of DNA Methylation and H3K27me3 in Mouse Embryonic Stem Cells

Abstract: Chromatin is separated into functional domains distinguished by combinatorial patterns of post-translational histone modifications and DNA methylation. Recent studies examining multiple histone modifications have found numerous chromatin states with distinct profiles of chromatin marks and functional enrichments. There are data showing coordinate regulation between DNAme and H3K27me3, which are both involved in the establishment and maintenance of epigenetic gene silencing, but the data are conflicting. Multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
94
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 54 publications
12
94
1
Order By: Relevance
“…While recent observations in both plant and animal systems revealed that removal of DNA methylation can profoundly influence the distribution of H3K27me3 (Mathieu et al 2005;Lindroth et al 2008;Wu et al 2010;Deleris et al 2012;Hagarman et al 2013;Reddington et al 2013), the fact that DNA methylation can indirectly induce H3K9 methylation in plants (Tariq and Paszkowski 2004) and animals (Jin et al 2011) raised the possibility that some, or all, of the observed effects were indirect. We therefore tested for possible effects of knocking out either the single N. crassa H3K9me3 methyltransferase dim-5 (Tamaru and Selker 2001;Tamaru et al 2003) or the single N. crassa DNA methyltransferase gene dim-2 (Kouzminova and Selker 2001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While recent observations in both plant and animal systems revealed that removal of DNA methylation can profoundly influence the distribution of H3K27me3 (Mathieu et al 2005;Lindroth et al 2008;Wu et al 2010;Deleris et al 2012;Hagarman et al 2013;Reddington et al 2013), the fact that DNA methylation can indirectly induce H3K9 methylation in plants (Tariq and Paszkowski 2004) and animals (Jin et al 2011) raised the possibility that some, or all, of the observed effects were indirect. We therefore tested for possible effects of knocking out either the single N. crassa H3K9me3 methyltransferase dim-5 (Tamaru and Selker 2001;Tamaru et al 2003) or the single N. crassa DNA methyltransferase gene dim-2 (Kouzminova and Selker 2001).…”
Section: Resultsmentioning
confidence: 99%
“…This is interesting given the mixed reports from animal cells about whether loss of facultative heterochromatin impacts constitutive heterochromatin. In a study using both undifferentiated and differentiated mouse ES cells, knockdown of Suz12 resulted in loss of H3K9me3, but only in the differentiated cells (de la Cruz et al 2007), while a separate study reported that Eed −/− -null, undifferentiated mouse ES cells showed both increases and decreases in 5mC at developmental genes (Hagarman et al 2013). Values represent the average of at least two technical replicates; dash indicates none detected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, Polycomb group (PcG) proteins that mediate H3K27me3 accumulation were reported to preferentially bind to CpG islands (Deaton and Bird, 2011;Ku et al, 2008;Woo et al, 2010), but DNA methylation reduces this binding (Hagarman et al, 2013;Wu et al, 2010). We therefore counted the number of low methylated CpG sites inside the K27HMDs and examined their relationship with H3K27me3 levels.…”
Section: Identification Of Hypomethylated Domains In the Medaka Genomementioning
confidence: 99%